Fire behaviour of deep beams under unsymmetrical loading - Fan, Shengxin (2022)
This paper focuses on the condition where a reinforced concrete (RC) deep beam is subjected to two concentrated loads (P1 and P2), which are positioned at respective distances a and c from bottom supports. In general, equal shear spans (a = c) and equal point loads (P1 = P2) are commonly assumed in most experimental programmes. Nevertheless, such cases are rare in practice. In contrast, due to the fact that deep beam floor normally subjects to irregular layout of column grid, deep beams are usually subjected to unequal load magnitude (load inequality or P1 ≠ P2) and unsymmetrical load positions (load asymmetry or a ≠ c). Although previous research has demonstrated the significant influences of load asymmetry and inequality on the structural performance of deep beams at room temperature, no research programme has been performed to study their influences on the fire performance of deep beams. As a result, this study is proposed to investigate the shear behaviour of unsymmetrically-loaded deep beams at fire condition, analytically and experimentally. The current research first derives a strut-and-tie-model (STM) to predict the shear capacity of RC deep beams under unequal/unsymmetrical loading conditions and at elevated temperatures. The STM takes into account the effects of unsymmetrical loading configurations, contribution of steel reinforcement on strut capacity, and thermal-induced gradient. Additionally, a test programme on six RC deep beams under fire condition is conducted for verification of the proposed model. Observations from this experimental programme show that load asymmetry and inequality have different effects on the fire performance of deep beams. To be more specific, an increase in load inequality leads to an alteration in failure mode of the deep beams, whist load asymmetry does not affect the failure mode as much. On the other hand, increasing load inequality can result in a significantly increased mid-span deflection at failure and a slightly increased failure time. Besides, effect of load inequality on deflection and failure duration depends on the loading positions. Furthermore, the proposed STM yields good agreement between test data and model predictions for unequally- and/or unsymmetrically-loaded deep beams, at both room and high temperatures.